Late Bleeding after Total Thyroidectomy: Report of Two Cases occurring 13 Days after Operation. Issue 6 (January 2013) - Calò, Pietro Giorgio; Erdas, Enrico; Medas, Fabio; Pisano, Giuseppe; Barbarossa, Michela; Pomata, Mariano; Nicolosi, Angelo
Postoperative hematoma is a rare but potentially life-threatening and unpredictable complication of thyroid surgery. We report two cases of very late postoperative bleeding occurring on the 13th postoperative day in patients treated with low-molecularweight heparin and acenocoumarol. Patient 1 was readmitted with complaints of progressive anterior neck swelling and bleeding from the cervical wound without respiratory distress. The patient had restarted therapy with Acenocoumarol associated with Nadroparin one day before. Under general anesthesia, cervical exploration allowed detection of a superficial hematoma. Patient 2 returned to our institution with subhyoid ecchymosis and moderate blood loss from the left drainage wound. The patient underwent drainage and was treated conservatively. Although most bleeding occurs within 24 hours, caution should be taken in patients on oral anticoagulants and low-molecular weight heparin and close monitoring should also be advised at home after discharge, particularly if anticoagulant therapy has restarted.